Comparative gene expression responses to Babesia infection and oil contamination in a seabird - Esperanza, Carlos W.; Quock, Rachel C.; Duerr, Rebecca S.; Roy, Scott W.; Sehgal, Ravinder N. M. (Frontiers in Conservation Science, 2024)
The common murre (Uria aalge) is a species of seabird particularly vulnerable to several environmental stressors, including parasitic infection and oil contamination. However, the molecular response to these stressors is severely understudied. This study investigated the common murre’s transcriptomic responses to these stressors. Blood samples were collected from common murres undergoing rehabilitation at International Bird Rescue in Fairfield, CA. Total RNA was extracted from these samples, followed by library preparation and Illumina sequencing to generate whole transcriptome data. Differential gene expression analysis was conducted using DeSeq2 to identify genes significantly altered in response to oil contamination and parasitic infection. Differential gene expression analysis revealed 194 genes shared between oil-contaminated and infected birds, including key immune-related genes, such as ANXA2, LY96, and LY86. These genes play vital roles in mediating the production of pro-inflammatory cytokines. Gene Set Enrichment Analysis indicated significant alterations in stress, immune, and inflammatory responses, with additional lipid metabolism changes in contaminated birds. Our findings highlight the detrimental effects that these stressors have on wild birds. These findings suggest a generalized stress response and specific metabolic adaptations to oil exposure, providing insights for seabird conservation.